Premature atrial contraction on Holter electrocardiogram predicts the recurrence of atrial fibrillation after catheter ablation. (3rd October 2022) - Sunaga, A; Tanaka, N; Masuda, M; Watanabe, T; Kida, H; Oeun, B; Sato, T; Sotomi, Y; Dohi, T; Okada, K; Mizuno, H; Nakatani, D; et al.
Abstract: Introduction: It is important to detect the recurrence of atrial fibrillation (AF) after catheter ablation (CA) early, but the method of detection has not been established. The purpose of this study is to determine whether 24-h Holter electrocardiogram (ECG) can predict the recurrence of AF after CA. Methods: We studied 336 patients of 497 patients enrolled in EARNEST-PVI trial to investigate whether the total number of premature atrial contraction (PAC) and the maximum number of PAC run by 24-h Holter ECG at 6 months after CA predicted AF recurrence after 6 months. We excluded 86 patients with recurrence by 6 months after CA and 75 patients without Holter ECG at 6 months after CA. Results: Median age was 66 years, male were 77% and median follow-up period was 1138 days. Receiver operating characteristic curve analysis identified the total number of PAC ≥270 beats and the maximum number of PAC run ≥8 beats as the optimal cutoff for prediction of AF recurrence. Kaplan-Meier analysis showed patients with the total number of PAC ≥270 beats had more frequent AF recurrence than those without (Kaplan-Meier estimated 3-year AF recurrence rate 34% vs. 17%, Log-rank P=0.001) and patients with the maximum number of PAC run ≥8 beats had more frequent AF recurrence than those without (Kaplan-Meier estimated 3-year AF recurrence rate 33% vs. 20%, Log-rank P=0.006). Multivariate analysis revealed that the total number of PAC ≥270 beats and the maximum number of PAC run were significantly associated with AF recurrence (hazard ratio [95% confidence interval] 1.83 [1.16–2.91], P=0.01 and 1.01 [1.01–1.02], P=0.001, respectively) Conclusion: The total number of PAC and the maximum number of PAC run on the Holter ECG may be useful in predicting AF recurrence after CA. Funding Acknowledgement: Type of funding sources: None.